West Germans Against The West - Müller, C. author. aut Link
X, 258 p.
Keywords: An exploration of how the theme of Anti-Americanism was employed by influential sections of the West German media to oppose the modernisation of the Federal Republic of Germany during the 'long 1950s'. In the public battle over the future direction of Germany, America stood as a symbol of social, political and economic corruption.